2014
DOI: 10.1097/mpg.0000000000000273
|View full text |Cite
|
Sign up to set email alerts
|

Virulence Factors and Antibiotic Resistance in Children With Helicobacter pylori Gastritis

Abstract: The cagE-positive and vacA s1a/m2 genotypes, which are correlated with increased antibiotic resistance, were predominant in our population. In countries where Hp infection is prevalent, studies focusing on virulence factors and antibiotic susceptibility may provide anticipation of the prognosis and may be helpful to reduce morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 35 publications
3
25
0
Order By: Relevance
“…The use of antibiotics for infections like gynecological, parasitic, or upper respiratory infections is considered a major risk factor for the development of resistance [50]. Changes in resistance profile over time may be caused by increased clarithromycin usage for pneumonia and decreased metronidazole usage for diarrhea because of a gradual increase in hygienic conditions nationwide [30]. Macrolide consumption is a significant problem in increasing clarithromycin resistance in H. pylori isolates.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The use of antibiotics for infections like gynecological, parasitic, or upper respiratory infections is considered a major risk factor for the development of resistance [50]. Changes in resistance profile over time may be caused by increased clarithromycin usage for pneumonia and decreased metronidazole usage for diarrhea because of a gradual increase in hygienic conditions nationwide [30]. Macrolide consumption is a significant problem in increasing clarithromycin resistance in H. pylori isolates.…”
Section: Discussionmentioning
confidence: 99%
“…In another southern region study, the clarithromycin resistance rate was found to be smaller at 8.9%, but the patients were living in rural areas with no history of macrolide use [28]. In two eastern region studies, the primary clarithromycin resistance rates were detected as 16.4 and 23.5% in 2008 and 2014, respectively [29,30]. The 2014 study included children who were 2 to 17 years old, and there was an increase in the primary clarithromycin resistance rates reported from the east region of Turkey [30].…”
Section: Prevalence Of Primary Clarithromycin Resistancementioning
confidence: 99%
See 2 more Smart Citations
“…18 . In 2014, 89 children were included in another study from a different part of Turkey and clarithromycin resistance was found to be 23.5% 19 . Factors such as the use of different methods, different ratios in using antibiotics for regions and the experience of people applying the method can be effective in identifying different resistant ratios in studies 20 .…”
Section: Discussionmentioning
confidence: 99%